Bilateral lower extremity amputation in a transgender female on estrogen therapy suffering from recurrent, medication-resistant arterial thrombi - Mitchell C. McDaniels, BS; Patrick D. Conroy, MD; Philip M. Batista, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
This case report presents a 40-year-old transgender female with a history of gender-affirming hormone therapy who experienced recurrent, medication-resistant arterial thrombi leading to bilateral lower extremity amputations. Despite multiple endovascular and surgical interventions, including bypass grafting and catheter-directed thrombolysis, the patient developed recurrent thrombotic events even while on anticoagulation therapy. Hematologic evaluation for coagulopathy was unremarkable. The case underscores the need for greater understanding of gender-affirming hormone therapy’s long-term cardiovascular effects while highlighting the challenges in managing arterial thrombosis in transgender patients. Further research is required to guide optimal anticoagulation strategies in this population.